Association of Clinical Signs and Symptoms with Abnormal Urinalysis Findings of Blunt Trauma Patients; a Cross-Sectional Study - Zarmehri, Bahram; Shouman, Ayeh; Pishbin, Elham; Jafari Chokan, Niaz-Mohammad; Najaf Najafi, Mona; Habibzadeh, Seyed Reza; Rayat Dost, Esmaeil; Foroughian, Mahdi (Archives of Academic Emergency Medicine, 2019)
Introduction: Urinalysis (UA) is performed routinely as a diagnostic screening test for trauma patients in most centers. This study aimed to examine the relationship between patients’ clinical signs and symptoms with UA findings. Methods: This cross-sectional study was carried out on multiple trauma patients between 18 to 65 years old, who were referred to the Emergency Department. UA was performed for all patients and its association with clinical signs and symptoms (pain, tenderness, abrasion, ecchymosis, hematoma, etc.) in abdomen, back, flank, and inferior hemi-thorax was evaluated. Results: 640 patients with the mean age of 39.8 ± 11.2 years were studied (65.0% males). 271 (42.4%) cases had associated injuries and 554 (86.6%) cases had at least one sign or symptom of trauma in abdomen, back, flank or inferior hemi-thorax. 146 (22.8%) patients had negative UA. Among cases with positive UA, 364 (56.9%) cases had microscopic hematuria with RBC < 25/HPF, 60 (9.4%) had microscopic hematuria with RBC ≥ 25/HPF and 70 (10.9%) had gross hematuria. None of the asymptomatic patients had microscopic hematuria with RBC ≥ 25/HPF and gross hematuria (p <0.001). Symptomatic patients who had signs in the abdomen, back or inferior hemi-thorax mainly had microscopic hematuria with RBC < 25/HPF, but those with signs in the flank, mainly had microscopic hematuria with RBC ≥ 25/HPF (p<0.001). Patients with pain, tenderness, abrasion, and ecchymosis in flank had a higher risk of positive UA findings (figure 2; p <0.001). Conclusion: Based on the findings of the present study, patients with any findings of pain, tenderness, abrasion, or ecchymosis in flank had higher risk of abnormal UA and perhaps urogenital injuries. None of the asymptomatic patients had microscopic hematuria with RBC ≥ 25/HPF and gross hematuria.